Phase‐Separated Polyzwitterionic Hydrogels with Tunable Sponge‐Like Structures for Stable Solar Steam Generation (Adv. Funct. Mater. 18/2023). (2nd May 2023) - Peng, Bolun; Lyu, Quanqian; Li, Miaomiao; Du, Shuo; Zhu, Jintao; Zhang, Lianbin
Abstract : Phase‐Separated Polyzwitterionic Hydrogels In article number 2214045, Lianbin Zhang and co‐workers construct a polyzwitterionic hydrogel evaporator with tunable sponge‐like structures by a phase separation strategy for stable solar steam generation. Owing to the anti‐polyelectrolyte effects and the highly interconnected pore structure, the evaporator enables adequate seawater uptake and transport to ensure a fast and stable water evaporation process.